Diamond-Like Carbon Film Deposition Using DC Ion Source with Cold Hollow Cathode - E. F. Shevchenko; V. A. Tarala; M. Yu. Shevchenko; A. A. Titarenko (Advances in Materials Science and Engineering)
Carbon diamond-like thin films on a silicon substrate were deposited by direct reactive ion beam method with an ion source based on Penning direct-current discharge system with cold hollow cathode. Deposition was performed under various conditions. The pressure (12–200 mPa) and the plasma-forming gas composition consisting of different organic compounds and hydrogen (C3H8, CH4, Si(CH3)2Cl2, H2), the voltage of accelerating gap in the range 0.5–5 kV, and the substrate temperature in the range 20–850°C were varied. Synthesized films were researched using nanoindentation, Raman, and FTIR spectroscopy methods. Analysis of the experimental results was made in accordance with a developed model describing processes of growth of the amorphous and crystalline carbon materials.